If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -6x = 24 + -3x Reorder the terms: -6x + 3y = 24 + -3x Solving -6x + 3y = 24 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -6x + 3x + 3y = 24 + -3x + 3x Combine like terms: -6x + 3x = -3x -3x + 3y = 24 + -3x + 3x Combine like terms: -3x + 3x = 0 -3x + 3y = 24 + 0 -3x + 3y = 24 Add '-3y' to each side of the equation. -3x + 3y + -3y = 24 + -3y Combine like terms: 3y + -3y = 0 -3x + 0 = 24 + -3y -3x = 24 + -3y Divide each side by '-3'. x = -8 + y Simplifying x = -8 + y
| 15(E-3)=-10(E+2) | | r(r)+3r=6 | | x^3+3x-14=0 | | 4(7-y)+2y=8 | | x+12=4x+52 | | 7=-3+3x | | =2x^2+2x-12 | | 4x+10y=1 | | 4x+7+6=-5x-23 | | -(8y+1)-(-7y-6)=1 | | =23x^2-22x | | 7x=84x | | 6(4x-9)=3(8x+5) | | 8+6r-7=7r+3-2r | | 8+6r-7r=7r+3-2r | | =(y-5)(y-3) | | A^3b^2= | | 4c^2+24c+30=0 | | =x^3-27 | | 2x+[3x-2(x-2y)-3x]= | | =15a^2+11a+2 | | 9x+6+4x+x-9= | | -3x-(2-x)=-2(2-3x) | | 13(t-4)+8t=7(3t+5)-8 | | 3(y+5)+5(y-4)+7= | | 15x^2-26x=0 | | 7(x-3)=7-2(3x+1) | | 4(y-5)= | | 9X+7X=81+X | | 3-2(4-x)=5(x+1)+2 | | 4mn-6m+5n-3m+4n-5mn= | | =x^2+19x+2 |